Mutuality in the duty of disclosure under the law of insurance / Samsuri Ishak - Ishak, Samsuri (Faculty of Law, 1986)
The general principles of the law of contract applies to insurance contracts as in other contracts. In fact an insurance contract is merely a special or specific type of contract. However, in applying the principles of the law of contract to insurance agreement in Malaysia, one has to be cautious as Malaysia has its own contract legislation. There had been the Contract (Malay States) Enactment, 1930, which was followed by the Contract (Malay States) Ordinance, 1950. These applied only to the Malay States. The law has now been made uniform for the whole of Malaysia by the Contract (Malay States) Amendment and Extension Act, 1974, and the 1950 Ordinance is now simply known as the Contracts Act, 19504. (Revised 1974) The specific rules and principles of the law of Insurance in Malaysia are instead governed by the Insurance Act, 1963 (Revised — 1972). This, therefore means that the English principles of contract cannot be applied per se. Where there is a specific provision in the Contracts Act or Insurance Act, that provision will have to be applied. English decisions would also be useful where the English law and the Malaysian Contracts Act are similar.